Effects of the degree of processing of insect ingredients in snacks on expected emotional experiences and willingness to eat. (December 2016) - Gmuer, Angelina; Nuessli Guth, Jeannette; Hartmann, Christina; Siegrist, Michael
Highlights: Insect snacks evoked negative emotional expectations that went beyond disgust. Positive emotional experiences were expected to be less frequent. Emotional evaluations significantly predicted willingness to eat. Caution should be used when developing products that contain whole insects. Snacks containing insects are far from being on a par with well-established products. Abstract: This study explored willingness to eat and the negative and positive emotional expectations that people from a Western country may have toward the consumption of insect snacks. The snacks, which were presented as pictures in an online survey, differed in their degree of processing of the insect ingredient: tortilla chips made of cricket flour ("flour"), tortilla chips containing deep-fried cricket bits ("bits"), a snack consisting of tortilla chips and deep-fried crickets ("mix"), and deep-fried crickets ("crickets"). Swiss respondents (N = 428) made 39 emotional evaluations, rated willingness to eat and expected liking of the presented products. Each participant evaluated the same non-insect-containing snack (within-subjects design) and one of four insect-containing snacks (between-subjects design). Results showed that the insect snacks evoked various negative emotional expectations that went beyond expectations of disgust. Positive emotional expectations were less expected to occur. Furthermore, expectations related to disgust / uneasiness, inertia / dissatisfaction, and positive emotional evaluations were significant predictors of willingness to eat. The degree of processing of the insect ingredient partly influenced the ratings, with the "mix" product being assessed more negatively than the "flour" or "bits" products. The "cricket" product was rated more positive than expected. The research indicates that in the development and marketing of insect food, efforts should be undertaken not only to eliminate initial negative expectations of disgust and dissatisfaction but also to generate positive emotional expectations. We suggest the marketing of snacks containing processed insect ingredients will be more promising, and selling whole insects alone is more preferable to selling a mixed snack. Regardless of the degree of processing of the insect ingredient, the results suggest that marketing activities must contend with a large emotional barrier.